Evenki of River Basin Olyokma: Resettlement and Land Use in the XXI Century - V. V. Filippova; A. N. Savvinova; G. Fondahl (Научный диалог)
The relevance of the study is due to the need to study the characteristics of the resettlement of the local Evenki group of the Olekma River Basin, which influenced the modern land use and economic and cultural relations of Evenki living now in the Olekminsky District of the Republic of Sakha (Yakutia), the Kalarsky and Tungiro-Olekminsky Districts of the Trans-Baikal Territory and the Tyndinsky District of Amur region. The article focuses on the study of the Evenki population dynamics based on a comparative analysis of the materials of the censuses of the 20th century. For comparison, current data on the number of Evenks in their areas of residence according to the 2010 census are given. An analysis of archival sources showed that changes in the resettlement of Evenk clans occurred simultaneously with changes in the administrative-territorial division. Factographic materials found in the National Archives of the Republic of Sakha (Yakutia) confirm that when deciding on the administrative-territorial structure, the opinions and proposals of the local population were taken into account. Author’s maps were compiled, which allowed a spatial analysis of the distribution of the population and the forms of organization of the Evenki economy. It was found out that each region has its own specific land use determined by administrative decisions and regional policies.